Ultrastructural profile of metapleural gland cells of the ant Atta laevigata (F. Smith, 1858) (Formicidae: Attini) - Vieira, Alexsandro Santana [UNESP]; Bueno, Odair Correa [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Brill Academic Publishers, 2012)
The metapleural gland is considered a synapomorphy of ants, and is characterized as a paired structure located at the two postlateral ends of the thorax and secretes substances capable of inhibiting and controlling fungi and bacteria in the fungus garden and inside the nest. This study was aimed at investigating if and which are the ultrastructural differences in the metapleural gland cells of workers (three castes) of Atta laevigata using transmission electron microscopy (TEM). This study revealed the presence of Golgi regions, rough endoplasmic reticulum (lamellar arid vesicular shapes), smooth endoplasmic reticulum, mitochondria (elongated, round-shaped), vacuoles, secretion granules with different electron densities, and myelin figures in the cytoplasm of secretory cells, indicating that this gland produces substances composed of proteins, lipids, and polysaccharides (glycogen in major workers). Lipid droplets and secretion granules were found very near to the microvilli, especially in minor workers. The intracellular portion of canaliculi exhibited invaginations that increased the surface area and modified the secretion produced by the secretory cells. In the three castes examined, the gland exhibited a reservoir preceded by a collecting chamber, both lined by a simple squamous epithelium with a cuticular intima. Workers of the three castes of A. laevigata might be involved in the production of secretion mainly composed of proteins with antibiotic properties and, minor workers, may be responsible for producing a wider variety of secretions compared 1.0 median and major workers in the colony. (C) Koninklijke Brill NV, Leiden, 2012.
Keywords: Attini; Atta laevigata; metapleural gland